Biochar mitigation potential in Norway estimated by IPCC Tier 1 and Tier 2 methods - Andreas Hagenbo; Adam O’Toole; Rasmus Astrup; Daniel Rasse (Carbon Management)
Biochar is a recalcitrant carbon-rich solid produced by pyrolysis of organic residues, and its application to soil is considered a promising approach to mitigate climate change, as biochar resists decomposition to readily contributes to soil carbon (C) sequestration. The IPCC provides a basis for future national-scale accounting of the changes in soil C stocks following biochar application to cropland soils. The IPCC Tier 1 approach for biochar is based on fixed emission factors to estimate biochar C sequestration. In contrast, the Tier 2 approach allows countries to use local emission factors and climate data to calculate the contribution of biochar to soil C sequestration. Accurate accounting of biochar C sequestration is essential for ensuring the credibility of C offsetting projects, as well as providing incentives for implementing biochar in C credit schemes, calling for comparative analyses of the different biochar Tier approaches. Here we retrieved biochar samples from local producers and measured their H/Corg to estimate the persistence of biochar in Norwegian croplands post application. Various feedstocks were considered, including forest residues, woody wastes, manure, sludge, and straw. For all biochar samples, the 100-year stable C fraction was calculated at ≥ 0.945, thus exceeding the default Tier 1 value (0.8). Biochar sourced from woody- and forestry residues had a Corg content above the default Tier 1 value (0.77). Based on this and data about national feedstock supplies, we compared the theoretical potential of biochar soil C sequestration to mitigate climate change in Norway, using the IPCC Tier 1 and Tier 2 approaches. Biochar C sequestration in soil was calculated at 0.79 Tg CO2-eq yr−1 and 0.92 to 0.96 Tg CO2-eq yr−1, respectively for the Tier 1 and Tier 2 approaches, thus, underlining that the choice of IPCC Tier approach can have a large impact on the estimated mitigation potential of biochar.